PERCEPTION OF ARABLE FARMERS ON USING WEB TOOLS FOR INFORMATION ACCESS IN SOUTH WEST NIGERIA: Usage, Web tools, Information, Farmers, Productivity - Adara, Christopher T.; Duntoye, B. T.; Uyamasi, I. M.; Asiyanbi, O. A.; Oyeyemi, P. O. (FUDMA JOURNAL OF SCIENCES, 2025)
As nations look to adopt more efficient production techniques, web tools such as WhatsApp, Facebook, Zoom and others is the contemporary paradigm for raising agricultural output globally. The study therefore described the socioeconomic characteristics of farmers, determined the farmers’ perception and usage of the web tools in accessing agricultural information. The study was carried out in south west Nigeria, using a multi-stage sampling technique among two hundred and ninety nine (299) arable farmers. Primary data were collected and analyzed using descriptive analysis. Result of analysis showed that most of the respondents were male, 46.8% had primary education with about 15 years of farming experience. The findings further found out that the farmers had positive perception towards web tools usage. The study therefore recommends that as a result of the positive disposition towards usage of web tools for accessing information, such tools should be designed in a user friendly manner by key players in ICT while also training the farmers in needed areas by extension agents.